Culturally inclusive prototyping for higher education institutions: navigating language and gender dynamics - Malkawi, Aminah Rezqallah; Abu Bakar, Muhamad Shahbani; Dahlin, Zulkhairi Md (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This article explores the crucial intersection of cultural inclusivity in designing and developing e-learning prototypes for Higher Education Institutions (HEIs) in developed countries, such as Saudi Arabia (SA), emphasizing language and gender dynamics. It delves into the deliberate design of prototypes that accommodate linguistic diversity and address gender biases prevalent in educational systems. Real-world examples illustrate innovative solutions institutions use to navigate the complexities of language and gender dynamics during the prototype design process. Notably, the prototypes discussed have undergone rigorous evaluation, ensuring they meet technical benchmarks while aligning with the diverse linguistic and gender aspects inherent to developed nations. By synthesizing cultural sensitivity with cutting-edge design, this article encourages educators, developers, and decision-makers to adopt holistic approaches in creating HEI prototypes. Incorporating cultural inclusivity fosters equitable learning environments and positions higher education to be both forward-thinking and deeply rooted in the cultural tapestry it serves.